Celebrating in King Otto’s Greece - Panayotis Kimourtzis; Anna Mandilara (Journal of Festive Studies)
The heavy-handed regime of King Otto of Bavaria introduced the ritual of national celebrations in Greece in 1833. The monarchy instituted annual celebrations for occasions such as the apovatíria—the anniversary of Otto’s landing in Nafplio—and also organized festivities for some of the king’s other public appearances (departures, arrivals, inauguration of various institutions). The festivities were primarily based on the traditions of European royal courts and secondarily on the protocol of the Orthodox Church. The monarchy and its concomitant institutions, the church (with its religious ceremonies) and the army (with its hierarchy), offered a familiar and safe spectacle with their firmly established rites such as parades, processions, hymns, and chants. Given the scanty financial resources of the Greek state during Otto’s reign, sponsoring such celebrations required a delicate balance. Focusing on the example of the anniversary of the Greek War of Independence on March 25, 1838, this article emphasizes the regime’s effort to stage said celebrations in a manner befitting both the significance of each event and the king’s grandeur without provoking public sentiment with the high cost of the celebrations or with events that were unfamiliar to the inhabitants of the Greek capital, Athens.